Comparison of echocardiographic parameters in Fabry cardiomyopathy and light‐chain cardiac amyloidosis. Issue 11 (24th September 2018) - Marek, Josef; Palecek, Tomas; Magne, Julien; Lavergne, David; Boulogne, Cyrille; Fadel, Bahaa M.; Jaccard, Arnaud; Linhart, Ales; Mohty, Dania
Abstract : Background: Fabry cardiomyopathy (FC) and light‐chain amyloid cardiomyopathy (AL) present with concentric left ventricular (LV) hypertrophy/remodeling and diastolic rather than systolic dysfunction. Direct comparisons are difficult due to rarity and confounded by variability of LV thickness. Aims: To compare LV diastolic and systolic properties between patients with FC and AL in a cohort matched for interventricular septal thickness (IVS). Methods: A two‐center echocardiographic analysis was performed, comprising 118 patients with IVS ≥12 mm (FC and AL 59 patients each) matched by IVS. Results: Fabry cardiomyopathy patients had larger LV end‐diastolic diameter (47.7 [44.0–50.9] vs 45.0 [41.5–49.0] mm, P = 0.002), better LV ejection fraction (EF 68.7 [63.4–74.0] vs 63.0 [54.0–70.0]%, P = 0.001) and midwall fractional shortening (midFS 14.8 [13.0–16.1] vs 12.1 [8.9–15.0]%, P = 0.006). LV EF <40% was rare in both (2% vs 7%, P = 0.17). AL patients expressed higher LV diastolic dysfunction grade (III in 26% vs 4%, II in 21% vs 12% and I in 54% vs 84%, P = 0.004), with higher E/e' ratio (13.6 [10.2–18.8] vs 9.8 [7.5–12.3], P < 0.0001). Average E/e' ratio and midFS were significantly associated with NYHA severity in both groups ( P < 0.05 for all). Conclusions: Matched AL patients had worse LV diastolic function than FC, driven by E/e'. Significant LV systolic dysfunction was rare overall. MidFS and E/e' were associated with heart failure severity in both groups.